2013
DOI: 10.3402/ijch.v72i0.21141
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-related knowledge, attitudes, and behaviours among Alaska Native people: a population-based study

Abstract: BackgroundSeveral studies have shown that Alaska Native people have higher smoking prevalence than non-Natives. However, no population-based studies have explored whether smoking-related knowledge, attitudes, and behaviors also differ among Alaska Native people and non-Natives.ObjectiveWe compared current smoking prevalence and smoking-related knowledge, attitudes, and behavior of Alaska Native adults living in the state of Alaska with non-Natives.MethodsWe used Alaska Behavioral Risk Factor Surveillance Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…While there are many reasons to continue smoking in spite of its well-documented consequences for health, many studies have shown or have done the research with underlying assumption that smokers misperceive the risks of smoking. 8 9 10 11 12 There are studies which have investigated whether smokers underestimate their health risks through the manipulated misleading beliefs about the smoking by tobacco companies. 9 10 12 Recently, there are studies attempting to answer how the knowledge, beliefs, and attitudes causes smokers to change their smoking behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are many reasons to continue smoking in spite of its well-documented consequences for health, many studies have shown or have done the research with underlying assumption that smokers misperceive the risks of smoking. 8 9 10 11 12 There are studies which have investigated whether smokers underestimate their health risks through the manipulated misleading beliefs about the smoking by tobacco companies. 9 10 12 Recently, there are studies attempting to answer how the knowledge, beliefs, and attitudes causes smokers to change their smoking behaviors.…”
Section: Introductionmentioning
confidence: 99%
“… 9 10 12 Recently, there are studies attempting to answer how the knowledge, beliefs, and attitudes causes smokers to change their smoking behaviors. 8 11 …”
Section: Introductionmentioning
confidence: 99%
“…In example, prevention for the human papillomavirus by way of the HPV vaccine was assessed in a focus interview study, and subjects reported that concerns over safety and lack of knowledge contributed to issues surrounding HPV vaccine acceptance within Northern Plains populations [56]. In a survey study, Alaskan Natives acknowledged awareness on dangers of smoking and a willingness to quit, but they were half as successful as non native Alaskan Natives [54]. Alaskan Natives also reported that tradition and culture in their indigenous population is a protective factor against suicide, though Alaskan Native suicide rates are much higher than the general US population [17].…”
Section: Current Issuesmentioning
confidence: 99%
“…Some households enforce at least partial bans that allow smoking in certain areas or at certain times and others enforce complete household smoking bans that prohibit smoking anywhere or any time in the home. Factors positively associated with complete household smoking bans include nonsmokers living or visiting in the home, higher household income, older age, two-parent households, availability of outdoor space, better awareness of harms related to SHS, workplace indoor smoking restrictions and presence of children in the home [411].…”
Section: Introductionmentioning
confidence: 99%
“…American Indians/Alaska Natives (AI/AN) have the highest prevalence of cigarette smoking (26%) compared to both Whites (19%) and Blacks (18%), and are disproportionately affected by tobacco-related diseases, such as heart disease and stroke [4, 1213]. Despite this disparity, not much is known about household smoking bans in this population and their SHS exposure is not well established [49, 11, 14–15]. This is problematic because tribes have a unique relationship with tobacco: tribal members often conceive tobacco as a sacred plant and use it ceremonially in spiritual practices, rituals, prayers and other cultural activities [16].…”
Section: Introductionmentioning
confidence: 99%